Румунський народний одяг: традиція і сучасність - Битке, М. (Народна творчість та етнологія, 2011)
The following study approaches the folk costume out of all the components of the Romanian culture and civilisation. Besides language, customs and traditions, the folk costume constitutes an emblem, a symbol, a point of reference, a fundamental identity constant that certifies the inclusion of its bearers into a certain cultural space that identifies and defines them spiritually. The folk costume is a material assembly with practical functions but also a cultural creation, imprinted with symbols and a pertinent communication means within the frame of the traditional rural community and, at the same time, an expressive visual language with multiple semantic valences.